ADVANTAGES AND DISADVANTAGES OF DISTANCE LEARNING, FROM EXPERIENCE IN A UNIVERSITY (American Journal of Pedagogical and Educational Research, 2025)
This article explores the real-world advantages and disadvantages of distance learning from the perspective of university-level implementation. Drawing on practical experiences, institutional data, and academic reflections, it offers a nuanced analysis of how distance learning has both empowered and challenged students, faculty, and administrators in the university setting.